PENGELOLAAN ALOKASI DANA DESA DI DESA SUNGAI AMBAWANG KUALA KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Gabryella O.P.M Simarmata E.42009075 (FISIP Universitas Tanjungpura Pontianak, 2013)
In specially, This research focus on village incomes that derived from Village Fund Allocation (ADD), which Management of Village Fund Allocation in village development include process such as Planning, Actuating and Controlling. Based on research who conducted by researcher in Village of Sungai Ambawang Kuala for 30% from total of Village Fund Allocation are good according to provision and existing regulation which most of the funds used for finance allowance / intensive village officials and BPD, then 70% from total of Village Fund Allocation more priority for physical development or village infrastructure such as construction of concrete roads rebates and renovation of village office. Researcher assessed that physical participation from villagers in planning process as well as implementation of activities who sourced from Village Fund Allocation (ADD) still less. Whereas in controlling of Village Fund Allocation (ADD) are realized with handover of Responsibility Report (LPJ) in terms of administration are still needed guidance and further training competency from controlling team at regency and sub-district for village government officials because all the way still not suitable with regulations inclue tardy to handover of Responsibility Report. Keywords : Management, Village Fund Allocation, Effective.